Social concepts in the time of William Shakespeare and their manifestations in Hamlet - Chumbay G., Julio; Garcia P., William
William Shakespeare, like any other writer, was influenced by many social concepts of his time to write his tragedies. But in Hamlet, one of the greatest tragedies of English Literature, is in which William Shakespeare focuses especially on such concepts. Practices, beliefs, politics, economy, culture, religion, and social norms or expectations of Elizabethan England are exposed in the tragedy of Hamlet. We can see these in the description of the settings and in the way of thinking, the reactions, and in the behavior of the characters during the development of the tragedy. All these social concepts manifested in Hamlet make the tragedy a mysterious work of great discussion in our days. Themes such us revenge, treason, ambition, love, murder, pre-arranged marriages and other matters exposed in Hamlet are resonant in Ecuadorian society nowadays too, and new perspectives concerning the tragedy are always being incorporated. The tragedy of Hamlet will keep alive for generations